Coupling of Algal Biofuel Production with Wastewater. (26th May 2014) - Bhatt, Neha Chamoli; Panwar, Amit; Bisht, Tara Singh; Tamta, Sushma
Abstract : Microalgae have gained enormous consideration from scientific community worldwide emerging as a viable feedstock for a renewable energy source virtually being carbon neutral, high lipid content, and comparatively more advantageous to other sources of biofuels. Although microalgae are seen as a valuable source in majority part of the world for production of biofuels and bioproducts, still they are unable to accomplish sustainable large-scale algal biofuel production. Wastewater has organic and inorganic supplements required for algal growth. The coupling of microalgae with wastewater is an effective way of waste remediation and a cost-effective microalgal biofuel production. In this review article, we will primarily discuss the possibilities and current scenario regarding coupling of microalgal cultivation with biofuel production emphasizing recent progress in this area.